Social Studies in Nigeria Through the Lens of Biesta’s Three Functions of Education - Njoku, Chimezie; Nwokah, Lawson Kemkamma (European Scientific Journal, ESJ, 2018)
This paper focuses on the examination of Social Studies Education in Nigeria with respect to the view of Gert Biesta’s three functions of education; qualification, socialization, and subjectification functions. It also discussed the concepts and definitions of Social Studies, the aims, goals and objectives of social studies in Nigeria, as well as the views of education by some scholars. Furthermore, the analysis and summary of Professor Biesta’s three functions of education were presented with emphasis on the socialization function. Comparison was drawn as well as the challenges of social studies in Nigeria. Recommendations were also made. Selected anthologies borrowed in the course of putting this paper together were also acknowledged.